Materials characterization : - Leng, Yang (J. Wiley, 2008)
This work is an illustrated introduction to modern characterization techniques, enabling users to understand the composition and structure of materials. Encompassing not just material structure but also chemical analysis, Materials Characterization covers all key structural and functional materials from metals and semiconductors to polymers and ceramics." "Materials Characterization is an introductory book ideal for scientists and engineers embarking on material-related research and development. It is also an essential tool for advanced undergraduate and postgraduate students taking a first course on the topic